2014
DOI: 10.1289/ehp.1307449
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Incidence of Hepatic Tumors in Adult Mice following Perinatal Exposure to Bisphenol A

Abstract: Background: Bisphenol A (BPA) is a high production volume chemical with hormone-like properties that has been implicated as a potential carcinogen. Early-life exposure has been linked to increased risk for precancerous lesions in mammary and prostate glands and the uterus, but no prior study has shown a significant association between BPA exposure and cancer development.Objective: We explored the effects of BPA exposure during gestation and lactation on adult incidence of hepatic tumors in mice.Methods: Isogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 36 publications
1
87
0
Order By: Relevance
“…BPA was associated with hypomethylation in human fetal livers, indicating that Esr1 methylation may be altered by BPA exposure but is not linked to the previously observed liver tumor phenotype. 3 DNA methylation at human homolog ESR1 decreased with low level BPA exposure and increased with higher exposure, supporting a potentially non-linear epigenetic response to BPA. These results support Esr1 as a potential target of BPA-induced DNA methylation change, but do not implicate this candidate gene as a candidate biomarker of both exposure and disease in this study.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…BPA was associated with hypomethylation in human fetal livers, indicating that Esr1 methylation may be altered by BPA exposure but is not linked to the previously observed liver tumor phenotype. 3 DNA methylation at human homolog ESR1 decreased with low level BPA exposure and increased with higher exposure, supporting a potentially non-linear epigenetic response to BPA. These results support Esr1 as a potential target of BPA-induced DNA methylation change, but do not implicate this candidate gene as a candidate biomarker of both exposure and disease in this study.…”
Section: Discussionmentioning
confidence: 88%
“…3 Offspring of virgin wild type (a/a) females and heterozygous (A vy /a) males were exposed during gestation and lactation to one of 3 doses of BPA (50 ng, 50 mg, or 50 mg BPA/kg maternal diet) or to a phytoestrogen-free control diet, as previously described. 3 Briefly, 6-week-old virgin wild type a/a female mice were randomly assigned to a phytoestrogen-free AIN-93G diet [TD.95092, with 7% corn oil instead of 7% soybean oil; Harlan Teklad, Madison, WI (composition available at http://www.harlan.com)] supplemented with one of 4 levels of BPA (0, 50 ng, 50 mg, or 50 mg /kg diet). The BPA was provided by the National Toxicology Program (NTP, Research Triangle Park, NC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these preliminary studies suggest that low‐dose BPA has the potential to pose health hazards. Recent studies have also aimed to evaluate the role of BPA in carcinogenesis,7, 22, 23 and have indicated that exposure to BPA may account, at least partially, for the increased incidence of multiple cancers, including breast cancer,24, 25, 26, 27 ovarian cancer,28, 29 uterine cancer,30 prostate cancer,31, 32 testicular cancer,33 and liver cancer 34. The carcinogenic effects of BPA are summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%